Digital Marketing Contribution On Performance Of Commercial Banks In Rwanda: A Case Study Of Bank Of Kigali - Eliab Mpora, Byamukama; Justin, Ngenzi Gatovu; Boaz, Kagabika (International Journal of Research, 2022)
The study assesses the digital market contribution on performance of commercial banks in Rwanda.This study employed a descriptive cross-sectional survey design where it was used to gather information on a population of 10 customers and 23 employees at a single point in time. The sample size was included by 10 staffs in sales department and 23 employees of marketing department from BK. The application of digital marketing helps in reducing marketing cost against traditional marketing in commercial banks in Rwanda where 30.0% in BK said that digital marketing reduces the cost at a very high level; while 70.0% respondents in BK said that digital marketing reduce the cost of marketing for Bank at a very high level.In a nutshell, according to the findings there is significant contribution of digital marketing on performance of commercial banks in Rwanda and Bank of Kigali in particular. As recommendation, the commercial banks in Rwanda should invest in digital platforms so as to be in a position to take full advantage of the digital marketing potential.